Secure virtual machine placement in cloud data centers - Lim, Gen Liang (2017)
The usage of cloud computing services is increasing popular and easier to set up. However, there are risks in setting up such servers. It would be risky to share server resources with unknown users over the Internet. Unknown users might launch ma- licious attacks on unknowning users residing in the same server resources, causing loss of information or denial of service. Thus, there is a need to separate such users. One of the means would be to allow users to set up their servers with se- curity criteria. Such as not to allow sharing of servers with unknown users. This would then add on extra constraints when allocating resources for the Virtual Ma- chine. However the allocation of virtual machines is a NP-Hard problem. The objective of the Final Year Project(FYP) is to adapt various allocation algorithms to allocate virtual machines with an added security constraint.